2004
DOI: 10.1093/intimm/dxh118
|View full text |Cite
|
Sign up to set email alerts
|

The role of Tyk2, Stat1 and Stat4 in LPS-induced endotoxin signals

Abstract: Mice lacking Tyk2, Stat1 or Stat4, which are members of the Jak-Stat signaling cascade, were resistant to LPS-induced endotoxin shock. Interestingly, Tyk2-deficient mice had higher resistance to LPS challenge than mice lacking either Stat1 or Stat4. The activation of MAPK and NF-kappaB by LPS, and the production of TNF-alpha and IL-12 after LPS injection, were not abrogated by the absence of Tyk2, Stat1 or Stat4. In Stat1-deficient mice, the induction of IFN-beta by LPS in macrophages was severely reduced, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 25 publications
7
64
0
2
Order By: Relevance
“…This discrepancy could be due to their different environmental settings, because although LPS induces HMGB1 release almost entirely through STAT-1 signaling in the cultured macrophages, other unknown processes such as cell necrosis (45) could also contribute to HMGB1 release in a JAK-dependent, but STAT-1-independent manner in in vivo settings. The evidence supporting the importance of JAK in LPS-induced lethality in vivo has been previously described in several reports, in which STAT-1 Ϫ/Ϫ mice are more susceptible to sepsis, compared with JAK protein tyrosine kinase family member-deficient Tyk2 Ϫ/Ϫ mice (28,29). Although we demonstrated that STAT-1 is critical in HMGB1 release, the detailed molecular mechanism of HMGB1 release via STAT-1 remains to be further characterized.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This discrepancy could be due to their different environmental settings, because although LPS induces HMGB1 release almost entirely through STAT-1 signaling in the cultured macrophages, other unknown processes such as cell necrosis (45) could also contribute to HMGB1 release in a JAK-dependent, but STAT-1-independent manner in in vivo settings. The evidence supporting the importance of JAK in LPS-induced lethality in vivo has been previously described in several reports, in which STAT-1 Ϫ/Ϫ mice are more susceptible to sepsis, compared with JAK protein tyrosine kinase family member-deficient Tyk2 Ϫ/Ϫ mice (28,29). Although we demonstrated that STAT-1 is critical in HMGB1 release, the detailed molecular mechanism of HMGB1 release via STAT-1 remains to be further characterized.…”
Section: Discussionsupporting
confidence: 85%
“…7E). In the case of survival, as previously reported (28,29), the survival rates of the STAT1 Ϫ/Ϫ mice compared with those of the B6 wild-type mice were increased only in low-dose LPS-treated group (20 mg/kg; Fig. 7F).…”
Section: Figure 6 No Is a Downstream Molecule Of Ifn-␤supporting
confidence: 82%
“…This effect was not limited to the down-regulation of IFN-␥; suppressive ODN also blocked the production of IFN-inducible protein-10, another gene regulated through the IFN-␤/STAT1 pathway (data not shown). Studies involving STAT1, STAT4, and Tyk2 knockout mice (TyK2 is a JAK that participates in the IFN-␤-and IL-12-mediated signaling cascade) demonstrate that these pathways contribute to LPS-induced endotoxic shock (26,40). Thus, interventions capable of targeting these signaling pathways should be of therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-␤ signaling and classic STAT1 trans-activator function in macrophages contributes to LPS-mediated toxicity in vivo (55,56). CpG DNA is less toxic than LPS in vivo, and the apparently antiinflammatory actions of alternatively activated STAT1 may be protective in this context.…”
Section: Figurementioning
confidence: 99%